PENGARUH PERILAKU KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN DI STARBUCKS COFFEE PIM 2 - Emenina; Rose Angel (Eduturisma, 2019)
Consumer behavior is an important factor in purchasing decisions. If the restaurant knows consumer behavior well, then the consumer will make a purchase and will later recommend to others. Therefore the purpose of this study is to determine whether the most influential consumer behavior factors and also purchasing decisions at Starbucks Coffee PIM 2. This study also aims to determine the effect of consumer behavior on purchasing decisions. Researchers distributed 100 questionnaires to Starbucks Coffee PIM 2 consumers with a simple random sampling method. The method in this study uses validity, reliability, descriptive statistics, average values, simple regression, coefficient of determination and hypothesis. Data processing using SPSS version 22.The results showed that the variable of consumer behavior (X) has a value of 3,989 and the purchase decision has a value of 4,201 (Y). There is a significant influence between consumer behavior on purchasing decisions at Starbucks Coffee PIM 2. Constant of 7.199, each increase in consumer behavior then the number of purchasing decisions increases by 0.868 times. The influence of consumer behavior on purchasing decisions by 84.3%